"Drumbeats, pennywhistles and all that jazz": the relationship between urban South African musical styles and musical meaning - Allen, Lara (African Music : Journal of the International Library of African Music, 1996)
In the forties, a pennywhistle was considered to be a child's toy: what small boys played because they could not afford 'real' instruments. What the quote I have just given illustrates particularly well is that from the sixties onwards, the pennywhistle and kwela music, the style which evolved around this instrument, had come to symbolise a whole era of South Africa's history. I would like to explain this extraordinary metamorphosis of meaning through an exploration of kwela's socio-political context and its effect on the style's development. As my theoretical springboard, I have taken Gramsci's notions of the relationship between culture and society's economic base. I explore this relationship using Chantal Mouffe's 'articulation theory' as modified for the study of popular music by Richard Middleton. I have further adapted Middleton's model, moulding it to the specific needs of the southern African situation.